EXPLORING HETEROGENEOUS TRAVEL BEHAVIOR RESPONSES TO CONGESTION PRICING WITH PP-SP SURVEY DATA: A CASE FROM JAPAN - Puspitasari, Silvia
Since the last few years, congestion pricing has become a concern for policy makers and academics in many fields around the world. This funding system has not only proven effective in reducing the level of congestion but also in maintaining the sustainability of the urban environment. Due to its efficiency, some cities/countries consider the possibility of applying the method, especially for car dependent city to promote better transportation system. To manage the dynamic traffic demand, it is necessary to study the user's reaction to the congestion pricing system to find out what behavioural changes might occur so it can be anticipated before the policy applied and facilitate it. This study will survey the preferences of road users under congestion pricing to alternative policy options. Utilizing the SP and PP surveys, this study created a model for capturing the heterogeneous travel behaviour responses under congestion pricing. Moreover, as further analysis, this study also demonstrates travel behaviour changes probability under different congestion pricing schemes (cordon and distancebased) and its relationship with attributes including price, time saving and egress in research area. This survey involved 1846 trips made by selected participants who regularly passing through CBD Area in Hiroshima CBD Area and Kumamoto CBD Area using cars. There are 6 alternative choices as a reaction to the application of congestion pricing including pay the charge, stop moving, change time zone, change destination, change transportation, and change route. In making the model, this research involves the Multinomial Logit method. The model was developed by looking at several factors that are considered to influence alternatives namely income, age, trip purpose, time saving, congestion price and egress as policy variable. Moreover, in this study a simulation was carried out involving attributes such as price of congestion, time saving and improvement of public transit (reducing of egress distance).ii The results obtained from this study indicate that the probability of travel behavior changes is more sensitive to price changes than changes in time saving or changes in egress. In addition, the Cordon and Distance-based schemes show differences in performance in reducing congestion in CBD areas spatially. Since the main goal of congestion pricing is to reduce congestion within CBD area, so distance-based schemes are preferable to applied in the CBD center. In addition, this study also considers the possibility of congestion pricing applications to reduce the number of visits to the CBD area, since change destination is one of the alternative options offered in the SP survey. Therefore, in maintaining the number of visits to the CBD area, this study concludes that the price of congestion will be more effective if there is an appropriate public transportation facility represented by the shorter egress distance that can be reached by road users.